Infância, educação infantil e relações étnico-raciais - Marlene de Araujo (2015)
This work aims at comprehending the relationships between childhood, child education as well as ethnic-racial relation by analyzing a set of national and local documents. The data will also be collected by means of manager, teacher, educators and family members who are responsible by the education of children from zero (0) to five (5) and responsible for implementing child education politics. So it is discussed in this context the childhood, the child education and ethnic racial relation from the perspective of the manager educator and mother. In the elaboration of this research object, it was tried to articulate broad themes as child study, post-colonial history studies, public politics and social movements. In this last case, a certain care was taken with the negro movement, mothers and other children s families belonging to a child education center as well as theoretical production of diversity for the right of ethnic-racial to education. This was all motivated to identify and discuss that the experiences of human being at child education school may propitiate child social and politics practices and their education. Associated to these questions it was proposed to identify / discuss the child education development at school that expresses the appreciation, negation and /or ignorance concerned to ethnic racial identities of children, mainly the black ones. The investigation corresponded to a qualitative research ant it was developed in a municipal early childhood center. It was used, so the following methodological strategies: semistructured interviews and focus groups. The study makes it clear that both educators and mothers recognize the presence of ethnic-racial prejudice within the scholar institution and that adverse effects black children construction, even though they are little understood in their manifestations and structural character of racism in the society. On the other hand, in the municipal and national official documents the reference even if it brief the ethnic-racial relations, however there is ignorance on the part of educators as well as on mothers in terms of their pedagogical practical implications towards teaching practice. Although all subjects involved in this research for seeking to construct a positive ethnic-racial identity the black mothers stand out in this regard.